ANALISIS FINANSIAL USAHA PENANGKAPAN IKAN DALAM MODEL PERBAIKAN KESEJAHTERAAN NELAYAN DI KABUPATEN ROKAN HILIR PROVINSI RIAU - Yafiz, M; Sondita, M Fedi A; Soemakaryo, Soepanto; Monintja, Daniel R (Jurnal Perikanan dan Kelautan, 2009)
The Regency of Rokan Hilir has huge potential of offshore fishingresources in a very strategic position in Malacca Strait. In order to gain amaximum benefit for the wealth of the fishermen, strategic mechanism ofmanagement is a necessity. The specific strategy should be based on holistic andcomprehensive model. So, to develope the model, information on offshorefinancial fishing performance is required. This research is aimed to measurefinancial indicators of eight kinds of offshore fishing methode, that are dominantin 4 districts in the Regency of Rokan Hilir, Riau Province, ie.: Sinaboi, Bangko,Kubu, and Pasir Limau Kapas. Data is collected from survey of 2.447 units ofoffshore fishing unit. Financial Analisys of activities are measured usingindicators: NPV, RTO, RTL, ROI dan PP. From 8 kinds of offshore fishingmethode, Five kinds are considered to be feasible. Those five kinds of methodeare payang, bubu, pengumpul kerang, jaring insang hanyut and handline; the rest,that are not feasible are jaring insang lingkar, pukat udang dan pukat pantai.Offshore fishing methode using jaring insang hanyut could be prioritized to bedevelop in this regency because it provided the highest income for the fishermen(NPV=56.432,719), the most productive (B/C ratio=2,00), highest investmentbenefit (IRR=57,53%), highest return of investment (RoI/=7,01) and the shortestpayback periode (PP=0,14). The application of Aplikasi development activitiesindeed has to consider the total income of every single individu involved on theactivities, not only the income of the owner of the unit activities. In general,government incentive in several format of subsidiasries for fishermen using thebeneficial methodes of oaffshore fishing.